The impact of changes to auditors' reporting and audit committee strength on bank directors' perceptions and decisions: An experimental investigation - Michelle Höfmann; Christiane Pott; Reiner Quick (International Journal of Auditing, 2023)
This study investigates the impact of two changes to the auditor's report - a separate section addressing going concern uncertainties (GCU section [GCUsec]) and information on management and auditor responsibilities - and the characteristics of the audit committee on bank directors' perceptions and decisions. In a 20.167em0.167em20.167em0.167em2 between-subjects experimental design with 85 German bank directors, we observe that a GCUsec in the auditor's report leads to more unfavourable decisions. Contrarily, explanations of responsibilities and different characteristics of the audit committee do not significantly impact on bank directors' perceptions and decisions. We thus confirm the effectiveness of the International Auditing and Assurance Standards Board (IAASB)'s revision of the International Standard on Auditing (ISA) 570 to enhance the informational value and decision usefulness of the auditor's report.
Keywords: 650; auditor's report; bank director; going concern uncertainty